C32 TRANSCATHETER LEAK OCCLUSION WITH ENDOVASCULAR COILS FOLLOWING LEFT ATRIAL APPENDAGE CLOSURE: PROCEDURAL SUCCESS AND OUTCOMES BEFORE AND AFTER LEAK CLOSURE. (18th May 2022) - Magnocavallo, M; Della Rocca, D; Lavalle, C; Mohanty, S; Carola, G; Bassiouny, M; Al–Ahmad, A; Burkhardt, D; Gallinghouse, J; Lakireddy, D; Horton, R; Di Biase, L; et al.
Abstract: Background: Whether residual peri–device leaks after left atrial appendage occlusion (LAAO) portend a higher risk of thromboembolism (TE), it is still a matter of debate. Objectives: We report the TE risk in patients with incomplete LAA closure before and after leak closure with endovascular coils. Methods: One hundred twenty–four Watchman patients with a significant (≥3mm) leak (mean age: 74 ± 9 years; 66.9% males; CHA2DS2–VASc: 4.4 ± 1.7; HAS–BLED: 3.1 ± 1) underwent LAA leak coiling. The expected annual TE risk was estimated based on the patients' CHA2DS2–VASc and compared with the annualized incidence observed before and after coiling (Fig.1B ). Results: The time between LAAO and leak coiling was 8±6 months [83 patients–year (PY)]; before leak closure, 6 (4.8%) patients had a TE event (annualized rate: 7.2%). Coil deployment was successful in all cases [median n. of coils deployed: 5 (IQR: 2–10)]. Procedure time was 79 ± 40 min; the mean volume of iodinated contrast medium used was 80 ± 43mL. The overall complication rate was 2.4% (1 pericardial tamponade, 2 pericardial effusion). Follow–up TEE after 61±14 days revealed complete LAA sealing or a negligible leak in 117 cases (94.4%); the remaining 7 patients had a moderate leak. During 14±6 months post–coiling (145 PY), 1 (0.8%) patient suffered from stroke. The incidence of TE events was significantly lower after leak closure than before coiling (0.8% vs 4.8%; log–rank p = 0.02; Fig.1A ). The annualized TE rates were 7.2% before and 0.7% after leak closure (Fig. 1A ). According to the expected rate estimated from the patients' CHA2DS2–VASc (9.8%), LAAO with and without significant leaks yielded to a risk reduction of 26.5% and 92.9% (Fig. 1B ). Conclusions: Transcatheter leak occlusion via endovascular coils was safe. LAA closure led to a significant reduction in TE events.